Helping teacher education students’ understanding of self-regulated learning and how to promote self-regulated learning in the classroom - Stephenson, Helen; Lawson, Michael J.; Nguyen-Khoa, Lan-Anh; Kang, Sean H. K.; Vosniadou, Stella; Murdoch, Carolyn; Graham, Lorraine; White, Emily (Frontiers in Education, 2024)
This research investigated the details and effects of a short online Professional Learning Program designed to develop teacher education students' knowledge about how to promote self-regulated learning (SRL) in the classroom. The Program was based on a new framework for how teachers can promote SRL, the SRL Teacher Promotion Framework (SRL-TPF), which focused on the promotion of SRL strategies, students' knowledge about learning, and students' metacognition. It consisted of seven modules describing the different SRL promotion types and SRL capabilities and ways to promote them through teacher talk and action. Modules included written information and video examples taken from observations of real classrooms, which were used to illustrate the transfer of SRL theory to instructional practice. Each module concluded with several assessment items. During the Program the participants, 91 teacher education students, were asked to take the role of researchers and use a simplified scoring system based on the SRL-TPF to code lesson transcripts taken from classroom observations. The results showed that by the end of the program over 85% of the participants were able to provide teacher instructions that included explicit SRL promotion and/or promoted students' SRL knowledge.